Genetic overlap between idiopathic pulmonary fibrosis and COVID-19. Issue 1 (7th July 2022) - Allen, Richard J.; Guillen-Guio, Beatriz; Croot, Emma; Kraven, Luke M.; Moss, Samuel; Stewart, Iain; Jenkins, R. Gisli; Wain, Louise V.
Coronavirus disease 2019 (COVID-19) is an infectious disease potentially leading to long-lasting respiratory symptoms and has resulted in over 4 million deaths worldwide. Idiopathic pulmonary fibrosis (IPF) is a chronic interstitial lung disease (ILD) characterised by an aberrant response to alveolar injury leading to progressive scarring of the lungs. Individuals with ILD are at a higher risk of death from COVID-19 [1]. Positive genetic correlations for COVID-19 and IPF point to interferon-mediated innate immunity in both response to infection and chronic disease whilst negatively correlated signals highlight implications for drug targeting https://bit.ly/37MMxZa